Tunneling spectroscopy in superconducting circuit lattices - Botao Du; Qihao Guo; Santiago López; Ruichao Ma (Physical Review Research)
We demonstrate tunneling spectroscopy of synthetic quantum matter in superconducting circuit lattices. We measure site-resolved excitation spectra by coupling the lattice to engineered driven-dissipative particle baths that serve as local tunneling probes. Using incoherent particle source and drain, we independently extract quasiparticle and quasihole spectra and reconstruct the spatial structure of collective excitations. We perform spectroscopy of a strongly interacting Bose-Hubbard lattice to measure changes in energy spectra for superfluid and Mott-insulator states at different densities and observe the effects of three-body interactions. Our results provide a toolset for characterizing many-body states in analog quantum simulators.